INFLUENCE OF TRANSFORMATIONAL LEADERSHIP STYLE ON EMPLOYEE SATISFACTION (Survey on the Departement of warehouse transport at PT. Xiong mao garment indonesia) - Rini Anggraeni; Dedi Mulyasana (Magister Manajemen Pascasarjana Universitas Langlangbuana, 2022)
Problems related to job satisfaction of employees in the warehouse department at PT. Xiong Mao Garment Indonesia includes 1) Tasks are not in accordance with responsibilities, 2) The work given is sometimes not in accordance with the skills possessed by employees 3) The work group does not support each other. each other 4) Sometimes the promotion of positions is not in accordance with the field under their control.The method used in this study is a quantitative method with a verification approach. The population used is the total number of Warehouse Angkut employees a total of 78 people. Using path analysis and SPSS ver.26.The results showed Transformational Leadership Style through the calculation of correlation coefficient analysis has a close and significant relationship with job satisfaction. Through the calculation of the coefficient of determination analysis, transformational leadership style, have a significant effect on employee job satisfaction.